THE EFFECT OF EMKM SAK IMPLEMENTATION ON TRUST TO OBTAIN WORKING CAPITAL CREDIT WITH TAX COMPLIANCE AS A MODERATING VARIABLE - Theresia Siregar; Aryani Aryani; Atik Djajanti (SEAN Institute, 2022)
This research aims to attest the benefit of SAK EMKM for small medium enterprises (SMEs) through approved banking loans and for the country through SME tax compliance, as well as the role of tax compliance as a mediator between SAK EMKM understanding and tax compliance. The data is obtained through questionnaires and samples are selected based on several criterias: 1) The business must fall into the category of a small medium enterprise 2) SMEs must be operating in Jabodetabek area, 3) SMEs must have prepared financial statements or bookkeepings periodically, and 4) SMEs must have attempted or possesses an ongoing loan from a bank. 74 samples are selected and analyzed using a mediated linear regression analysis with a 95% confidence interval. Results of analysis using IBM SPSS Statistics 23 and PROCESS macro showed that 1) SAK EMKM has a positive significant effect on the amount of loan accepted by the bank, 2) SAK EMKM has a positive significant effect on SME tax compliance, and 3) tax compliance does not mediate the relationship between SAK EMKM understanding and SME tax compliance.